Development and validation of the Measure of Indigenous Racism Experiences (MIRE) - Paradies Yin C; Cunningham Joan (BMC, 2008)
Abstract Background In recent decades there has been increasing evidence of a relationship between self-reported racism and health. Although a plethora of instruments to measure racism have been developed, very few have been described conceptually or psychometrically Furthermore, this research field has been limited by a dearth of instruments that examine reactions/responses to racism and by a restricted focus on African American populations. Methods In response to these limitations, the 31-item Measure of Indigenous Racism Experiences (MIRE) was developed to assess self-reported racism for Indigenous Australians. This paper describes the development of the MIRE together with an opportunistic examination of its content, construct and convergent validity in a population health study involving 312 Indigenous Australians. Results Focus group research supported the content validity of the MIRE, and inter-item/scale correlations suggested good construct validity. A good fit with a priori conceptual dimensions was demonstrated in factor analysis, and convergence with a separate item on discrimination was satisfactory. Conclusion The MIRE has considerable utility as an instrument that can assess multiple facets of racism together with responses/reactions to racism among indigenous populations and, potentially, among other ethnic/racial groups.